Wortbildung diamedial Korpusstudien zum geschriebenen und gesprochenen Deutsch - Stumpf, Sören (Reihe Germanistische Linguistik, 2023)
The book is devoted to word-formation in written and spoken German. Corpus analyses trace diamedial usage patterns and functions of word formations in single texts, text complexes, text types as well as in linguistic interaction. From a theoretical point of view, the study draws on textual and interactional linguistic approaches as well as cognitive semantic and constructional grammatical approaches.